Gunungsitoli City Planning Study towards Smart City in Nias Islands - Ikhtiar Aronifati Daeli; Sri Pare Eni; M. Maria Sudarwani (Budapest International Research and Critics University, 2022)
Gunungsitoli is the oldest and largest city in the Nias Islands. The status of Gunungsitoli City was upgraded from a sub-district to an autonomous city, based on Law Number 47 of 2008. Currently, Gunungsitoli City is the gateway and driving force for the economy, trade and education in the Nias Islands which has the potential of natural, marine, and land resources that are very broad. The description of the problem of the Gunungsitoli City Planning Study towards a Smart City, the problems discussed in this proposal include the understanding of smart cities/smart cities related to regional development strategies, the Smart City concept is also indeed presented as an answer for efficient resource management. Qualitative research methods were chosen to solve the problems faced in planning Smart City. In the Gunungsitoli Urban Planning Study Towards a Smart City Case Study: Nias Islands. The problem limitation in this City Design (Research Studio 2) task is the concept of a service-based smart city structure, which is transparent and plays a role in making it easier for the public to get information quickly and accurately.